DIFFERENCES IN STUDENT LEARNING OUTCOMES WITH COMPUTER-BASED LEARNING MODELS TUTORIAL TYPE AND ASSIGNMENT METHODS ON TIME UNIT CALCULATION OPERATIONS IN CLASS V STATE ELEMENTARY SCHOOL 13 CINGKARIANG - fahreza, angga; masniladevi, masniladevi; Arlis, Syamsu (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
The background of this research is the fact that teaching teachers are still using assignment learning methods, learning activities that take place in the classroom tend to be teacher-centered so that the learning process is less attractive to students. This study aims to determine the differences in the use of the tutorial type computer-based learning model with the assignment method on student learning outcomes in the operating material to calculate the unit of time in class V SDN 13 Cingkariang. This type of research is an experiment in the form of Quasi Experimental Type Nonequivalent Control Group Design. The population in this study were all fifth grade students of SD Negeri 13 Cingkariang. The sampling technique uses Total Sampling. The sample used in this study was VA class 21 students and 21 VB class students. The technique used to determine the experimental and control groups is through simple draws. VB class was determined as the experimental group and VA class as the control group. The instrument used was a test. The data analysis technique in this study uses a prerequisite test in the form of a normality and homogeneity test as well as a hypothesis test using the t-test (independent sample test). Based on the research that has been done, then tcount> ttable is obtained, 1.92226> 1.684 with α = 0.05 which means Ha is accepted. The average student learning outcomes measured by post test after learning, namely in the experimental class 83.80 and the control class 76.50. So that Ha is accepted, namely there are differences in the use of demonstration methods with lecture methods on student learning outcomes in human sensory material in class V SDN 13 Cingkariang.